Effect of Processing Parameters on the Physical Characteristics of Palm Oil-Based Table Margarine - Mat Sahri, Miskandar (2002)
The optimum processing conditions are as important as the product formulation in margarine production. However, the effects of the processing parameters, especially the emulsion temperature, flow rate, product temperature and pin-worker speed, have not yet been thoroughly investigated. This study, using a scraped-surface tube cooler pilot plant, investigated the effects of these parameters on a palm oil-based margarine during its processing and storage. The processing conditions mainly affected the marganne through its consistency by influencing the solid fat content (SFC) and the crystal polymorph formed. At temperatures of 40°C, 45°C and 50°C, there was no SFC in the emulsions, but 15.9%, 13.9% and 15.6% were formed in the tube cooler, respectively. The emulsion temperature had no significant effect on the product during storage, although some differences were observed during processing. A margarine with stable consistency and SFC, a moderately high softening point and in the β-polymorph was formed from the emulsion at 45°C. The margarine consistency was the highest at 15 kg/hr emulsion flow rate, and the lowest at 4S kg/hr. Margarine processed at tube cooler temperature 25°C produced an unusual hardening with formation of the β-crystal polymorph in the second week of storage. At 15°C and 20°C it remained in the β-crystal form for four and three weeks, respectively. The SFCs developed in the tube cooler at the pin-worker speeds of 100 and 300 RPM were 9. 12% and 10.11%, respectively. The higher speed retained the emulsion longer in the tube cooler, allowing more crystal formation. The SFCs after the pin-worker at 100 and 300 RPM were 9.01% and 8.72%, respectively. The higher speed severely destroyed the crystal structure, lowering the SFC. The consistency of the margarines at the pin-worker speeds of 100, 200 and 300 RPM were 214,210.4 and 204 g/cm2, respectively. They were already in a mixture of β' and β crystal forms in the first week after production. The study suggests that margarine manufacturers using 100% palm oil should use an emulsion temperature of 45°C, emulsion flow rate at 100% of the plant capacity, pin-worker speed of 200 RPM and chilling temperature of the scraped surface tube cooler of 20°C.